2014
DOI: 10.4172/2161-0495.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Oral Application of Charcoal and Humic acids to Dairy Cows Influences Clostridium botulinum Blood Serum Antibody Level and Glyphosate Excretion in Urine

Abstract: The present study was initiated to investigate the influence of oral application of charcoal, sauerkraut juice and humic acids on chronic botulism in dairy cows. A total of 380 Schleswig Holstein cows suffering from chronic botulism were fed daily with 400 g/animal charcoal for 4 weeks (1-4 weeks of study), 200 g/animal charcoal (5-10 weeks of study), 120 g/animal humic acid (11-14s week of study), 200g charcoal and 500 ml Sauerkraut juice/animal (13-16 weeks of study), 200 g charcoal and 100 mL Aquahumin/anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
0
17
0
2
Order By: Relevance
“…Biochar, wood vinegar (i.e., aqueous solutions of condensed pyrolytic gases) and humic substances can act as redox buffering substances (Husson, 2012; Kluepfel et al, 2014) which may explain why the feeding of biochar, pyrolytic vinegar and humic substances often show similar effects; and why the blending of biochar with wood vinegar or humic substances seems to reinforce the effects (Watarai, Tana & Koiwa, 2008; Gerlach et al, 2014). However, unlike both dissolved organic substances, biochar provides a highly porous framework with high specific surface area, where humic-like substances or pyrolytic vinegar can be adsorbed and unfurl three-dimensionally as a coating of the inner-porous aromatic carbon surfaces of biochar.…”
Section: Resultsmentioning
confidence: 99%
“…Biochar, wood vinegar (i.e., aqueous solutions of condensed pyrolytic gases) and humic substances can act as redox buffering substances (Husson, 2012; Kluepfel et al, 2014) which may explain why the feeding of biochar, pyrolytic vinegar and humic substances often show similar effects; and why the blending of biochar with wood vinegar or humic substances seems to reinforce the effects (Watarai, Tana & Koiwa, 2008; Gerlach et al, 2014). However, unlike both dissolved organic substances, biochar provides a highly porous framework with high specific surface area, where humic-like substances or pyrolytic vinegar can be adsorbed and unfurl three-dimensionally as a coating of the inner-porous aromatic carbon surfaces of biochar.…”
Section: Resultsmentioning
confidence: 99%
“…Gerlah et al [54] fed <8 mm diameter charcoal with other supplements to dairy cows at different doses, and investigated the effect of the treatment on blood serum C. botulinum ABE and CD antibody levels. A daily application of 400 g of charcoal (1)(2)(3)(4) week of the experiment) and 200 g of charcoal with 50 mL of sauerkraut juice (11)(12)(13)(14) week of the experiment) per entire herd significantly reduced the antibody levels by about 30% due to the absorption of C. botulinum toxins in the gastrointestinal tract by the charcoal.…”
Section: Biochar As a Feed Additivementioning
confidence: 99%
“…The process yields two main products, biochar, constituting 50% of the carbon content of the biomass, and biofuel, often syngas which can be employed in several energy application processes (Anita, 2009;Almuth, 2011). Gerlach et al (2014b) and Van et al (2006a) reported that dietary inclusion of biochar is capable of enhancing the immune status of animals. According to Gerlach and Schmidt (2012) inclusion of biochar in the diet of broiler birds deactivated toxins found in the digestive tract, helped activate intestinal flora and resulted in improved vitality of the birds.…”
mentioning
confidence: 99%